Revitalisasi pola pembelajaran Pendidikan Agama Islam di perguruan tinggi sebagai upaya konstruktif membangun karakter mahasiswa - Kholidah, Lilik Nur (2014)
Abstract : The implementation of an Islamic education teaching in the university education curriculum plays an important role as both in intellectual and social. Not only limited for religious messages delivery, but also as a cultural de-veloper and a national character builder. For this reason, it is needed to do some revitalization on Islamic education, to make it relevant with socio-cultural dy-namics. Revitalization, as mentioned in this paper, emphasizes on reformula-tion of Islamic education learning paradigm and its instructional approach as an effort to build a student character. Keywords : revitalization, teaching, Islamic education